PS-BPP02-4: DIFFERENCES IN RISK FACTORS FOR DEVELOPING HYPERTENSION WHEN HYPERTENSION REFERENCE VALUES ARE CHANGED. (January 2023) - Sakoda, Takashi; Akasaki, Yuichi; Kawasoe, Shin; Kubozono, Takuro; Sasaki, Yuichi; Ikeda, Yoshiyuki; Ohishi, Mitsuru; Miyahara, Hironori; Tokushige, Koichi
Abstract : Objective: In 2017, the American College of Cardiology (ACC) and the American Heart Association (AHA) lowered the diagnostic reference value for hypertension to 130/80 mmHg. On the other hand, the Japan Society of Hypertension (JSH) Guidelines for the Treatment of Hypertension 2019 set the diagnostic reference value at 140/90 mmHg because there is insufficient evidence to set it at 130/80 mmHg in Japan. We sought to determine whether there were differences in risk factors predicting future development of hypertension if the diagnostic threshold were lowered in Japan. Method: Of 137, 308 subjects who underwent health checkup between 2007 and 2015, 18, 657 middle-aged men who were observable for 5 years were included in the study. First, we adapted the JSH2019 criteria and used nominal logistic regression analysis to explore factors involved in the development of hypertension in normotensive subjects who are judged to be normotensive at the first checkup and hypertensive 5 years later. Age, systolic blood pressure, diastolic blood pressure, BMI, uric acid, LDL, HDL, triglycerides, HbA1c (JDS), eGFR, smoking history, daily drinking habit were used as factors for adjustment. Next, the ACC/AHA2017 criteria were adapted and analyzed using the same method to examine the differences in relevant factors from the adaptation of the JSH2019. Results: 12, 296 subjects were considered normotensive at first checkup according to JSH2019 criteria. After 5 years, 2, 568(20.8%) were diagnosed with hypertension. Age [OR = 1.04, CI = 1.03–1.05, p < 0.001], BMI [OR = 1.08, CI = 1.03–1.13, p < 0.001], uric acid [OR = 1.11, CI = 1.06–1.16, p < 0.001], HbA1c(JDS) [OR = 1.19, CI = 1.10–1.28, p < 0.001], and daily drinking habit [OR = 0.75, CI = 0.66–0.86, p < 0.001] were associated with development of hypertension at 5 years. On the other hands, 7, 892 subjects were considered normotensive at first checkup when AHA/ACC2017 criteria were adapted. After 5 years, 5.549(45.1%) were diagnosed with hypertension. Age [OR = 1.03, CI = 1.01–1.04, p < 0.001], BMI [OR = 1.08, CI = 1.02–1.14, p = 0.006], uric acid [OR = 1.15, CI = 1.08–1.21, p < 0.001] and daily drinking habit [OR = 0.69, CI = 0.60–0.80, p < 0.001] were associated with development of hypertension at 5 years. Conclusions: Adapting the AHA/ACC2017 criteria will result in more people developing hypertension than the JSH2019 criteria. Aging, elevated uric acid, and daily drinking habits are risk factors that predict future hypertension, even according to the AHA/ACC2017 criteria.